Plasma homocysteine and ischemic stroke patients in Thailand - Tasanee Tantirittisak (2018)
Background: Hyperhomocysteinemia was recently found to be a risk factor for stroke; however, the available data from Thailand is scarce. Objective: To study plasma homocysteine levels in ischemic stroke and compare it with age-and sex-matched controls, and to identify the association of plasma homocysteine and subtype of stroke. Material and Method: The authors studied plasma homocysteine levels of ischemic stroke patients with clinical signs and symptoms of stroke as confirmed by CT scan and compared them with control subjects who presented with other diseases and no clinical signs and symptoms of stroke between June 2000- May 2001 in Prasat Neurological institute. Fasting plasma homocysteine was measured by HPLC technique. Abnormal cut off point of plasma homocysteine was identified and associations of plasma homocysteine and stroke were studied by using logistic regression analyses. Results: Two hundred and sixty-eight patients were recruited in the present study (132 controls and 136 ischemic stroke patients). The abnormal cut off point of plasma homocysteine was > 14 μmol/L. The authors found statically significant association of abnormal plasma homocysteine and stroke (p<0.001) with odds ratio of 4.277 (95%CI 2.551-7.171). After adjusting the confounding factor, the authors found that high homocysteine was significantly associated with ischemic stroke (p<0.001) with odd ratio of 3.401 (95%CI 1.954-5.922). In the subgroup analyses of type of stroke and abnormal homocysteine, the authors demonstrated that abnormal homocysteine levels were more pronounced in the large vessel subtype than the small group. Conclusion: Abnormal homocysteine level is an independent risk factor of ischemic stroke and more correlated with large vessel subtype.